(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The moments that preceded the 2022 Brazilian presidential elections were defined by an intense and unprecedented political polarization between the democratic forces led by the former President Lula and the far-right faction led by the then in office President Bolsonaro. The aim of this chronicle is to analyze the historical context of this polarization, the facts that took place on the day to day of the election process, some of the proposals and debates occurred between both candidates, as well as the consequences of Lula’s narrow victory over Bolsonaro’s brand of ‘neofascism’ for the country at large.